2014
DOI: 10.1037/lhb0000037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the psycholegal abilities of young offenders with fetal alcohol spectrum disorder.

Abstract: Individuals with a diagnosis of fetal alcohol spectrum disorder (FASD) experience a range of physical, cognitive, and behavioral deficits thought to interfere with their ability to competently navigate the arrest, interrogation, and trial process. This study examined the psycholegal abilities of young offenders with FASD, including their understanding and appreciation of Miranda rights, and adjudication capacities (factual knowledge of criminal procedure, appreciation of the nature and object of the proceeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 60 publications
1
64
0
Order By: Relevance
“…Central among these efforts should be the development of purpose-built forensic screening instruments for TBI. defendant's ability to successfully navigate the criminal justice process [29]. Such impairments can include affective dysregulation (e.g., mood disorders), anxiety, psychosis, impulsivity, and behavioral problems [4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Central among these efforts should be the development of purpose-built forensic screening instruments for TBI. defendant's ability to successfully navigate the criminal justice process [29]. Such impairments can include affective dysregulation (e.g., mood disorders), anxiety, psychosis, impulsivity, and behavioral problems [4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…There has been relatively little empirical investigation into the impact of an defendants FASD on their competency to stand trial (CST). However, from the sparse literature to date, FASD symptoms are likely to have a negative affect on a defendant's CST (e.g., Brown et al, 2017;Freckelton, 2016;McLachlan et al, 2014). The assessment of CST is complicated given the broad range of how neurocognitive and adaptive functioning impaired which are associated with PAE can present.…”
Section: Fasd and Competency To Stand Trial (Cst)mentioning
confidence: 99%
“…Assessment of CST, despite the challenges, is nevertheless imperative to the protection of due process rights (Brown, Haun, Novick Brown, & Zapf, 2016;Brown et al, 2017;McLachlan et al, 2014-see Brown, Carter, Haun, Wartnik, & Zapf, 2019. Individuals with FASD can very easily appear to meet minimal criteria for CST when in fact they have nuanced or subtle impairments that may lead to significant problems for proceeding in the criminal justice system.…”
Section: Fasd and Competency To Stand Trial (Cst)mentioning
confidence: 99%
“…Only two studies were identified which investigated the psycho-legal abilities of offenders with FASDs [8,39]. In a group of young offenders with FASDs, McLachlan, et al [8] investigated the psycho-legal abilities relevant to interrogation and adjudication in addition to assessing the offender's insight and confidence regarding their psycho-legal abilities.…”
Section: Evaluating the Psycho-legal Abilities Of Young Offenders Witmentioning
confidence: 99%